2019
DOI: 10.1042/cs20181064
|View full text |Cite|
|
Sign up to set email alerts
|

BMSC-derived exosomes carrying microRNA-122-5p promote proliferation of osteoblasts in osteonecrosis of the femoral head

Abstract: Mesenchymal stem cells (MSCs) with multipotential differentiation capacity can differentiate into bone cells under specific conditions and can be used to treat osteonecrosis (ON) of the femoral head (ONFH) through cell transplantation. The current study aims to explore the role of bone marrow (BM) MSCs (BMSCs)-derived exosomes carrying microRNA-122-5p (miR-122-5p) in ONFH rabbit models. First, rabbit models with ONFH were established. ONFH-related miRNAs were screened using the Gene Expression O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 58 publications
4
105
0
1
Order By: Relevance
“…Utilizing exosomes derived from different stem cells has recently become a popular area of research for treatment of ONFH [ 18 , 19 , 37 ]. Our previous research has revealed the widespread blood supply network of the femoral head [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing exosomes derived from different stem cells has recently become a popular area of research for treatment of ONFH [ 18 , 19 , 37 ]. Our previous research has revealed the widespread blood supply network of the femoral head [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of ONFH caused increased expression of angiogenic responses-related genes, which were implicated in HIF-1, PI3K-Akt, and MAPK signaling pathways [39]. Mesenchymal stem cellsderived exosomal miR-122-5p protects against ONFH progression by triggering the RTK/Ras/ MAPK signaling pathway [17]. Here, our ndings indicated that miR-150-5p-overexpressed BMSC exosomes may ameliorate ONFH by promoting angiogenesis via these signaling pathways.…”
Section: Discussionmentioning
confidence: 55%
“…Next, we investigated whether exosomes overexpressed miR-150-5p could regulate angiogenesis. BMSC exosomes have been demonstrated to display therapeutic effect on various diseases including osteonecrosis [22], so we chose BMSC exosomes as miR-150-5p transporter. We rst evaluated the action of BMSC exosomes in angiogenesis.…”
Section: Bmsc Exosomes Promote Endothelial Cell Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing exosomes derived from different stem cells has recently become a popular area of research for treatment of ONFH [19,37,38]. Our previous research has revealed the widespread blood supply network of the femoral head [39].…”
Section: Discussionmentioning
confidence: 99%